Magnesium intake and colorectal cancer risk in the Netherlands Cohort Study - van den Brandt, P A (Nature Publishing Group, 2007)
Energy-adjusted magnesium intake was nonsignificantly inversely related to risk of colorectal cancer (n=2328) in the Netherlands Cohort Study on Diet and Cancer that started in 1986 (n=58 279 men and 62 573 women). Statistically significant inverse trends in risk were observed in overweight subjects for colon and proximal colon cancer across increasing quintiles of magnesium uptake (P-trend, 0.05 and 0.02, respectively). Although an overall protective effect was not afforded, our results suggest an effect of magnesium in overweight subjects, possibly through decreasing insulin resistance.